Commercially Available Nitrate Ionophores in Potentiometric Sensors are not Superior to Common Ion‐exchangers. Issue 2 (3rd August 2022) - Damala, Polyxeni; Zdrachek, Elena; Bakker, Eric
Abstract: Nitrate sensing is an important application for potentiometry in environmental applications. Its recognition is by ion‐exchangers whose selectivity is governed by the lipophilicity of the ions in solution. Yet, considerable research efforts have been dedicated to the development of such ionophores and some have already been commercialized. This work examines two commercially available nitrate ionophores, nitrate ionophores V and VI, and compares their performance with widely used ion‐exchangers by determining the resulting membrane selectivity and complexation to nitrate. Unfortunately, adding a nitrate ionophore to the membrane did not result in improved selectivity. Sandwich membrane experiments indicated that binding interaction is too weak to be measurable, with a logarithmic formation constant of just 1.36±0.14 for ionophore V with nitrate. Ways to improve the reporting of relevant data are suggested. Abstract :